Intersections in Neuropsychiatric and Metabolic Disorders: Possible Role of TRPA1 Channels - Sodhi, Rupinder Kaur; Singh, Raghunath; Bansal, Yashika; Bishnoi, Mahendra; Parhar, Ishwar; Kuhad, Anurag; Soga, Tomoko (Frontiers in Endocrinology, 2021)
Neuropsychiatric disorders (NPDs) are a huge burden to the patient, their family, and society. NPDs have been greatly associated with cardio-metabolic comorbidities such as obesity, type-2 diabetes mellitus, dysglycaemia, insulin resistance, dyslipidemia, atherosclerosis, and other cardiovascular disorders. Antipsychotics, which are frontline drugs in the treatment of schizophrenia and off-label use in other NPDs, also add to this burden by causing severe metabolic perturbations. Despite the decades of research, the mechanism deciphering the link between neuropsychiatric and metabolic disorders is still unclear. In recent years, transient receptor potential Ankyrin 1 (TRPA1) channel has emerged as a potential therapeutic target for modulators. TRPA1 agonists/antagonists have shown efficacy in both neuropsychiatric disorders and appetite regulation and thus provide a crucial link between both. TRPA1 channels are activated by compounds such as cinnamaldehyde, allyl isothiocyanate, allicin andmethyl syringate, which are present naturally in food items such as cinnamon, wasabi, mustard, garlic, etc. As these are present in many daily food items, it could also improve patient compliance and reduce the patients' monetary burden. In this review, we have tried to present evidence of the possible involvement of TRPA1 channels in neuropsychiatric and metabolic disorders and a possible hint towards using TRPA1 modulators to target appetite, lipid metabolism, glucose and insulin homeostasis and inflammation associated with NPDs.